Analisis Kekerasan pada Press Cage Setelah Perlakuan Panas Dengan Suhu 8500c Quenching Dengan Oli Sae 40 Dan Air Laut - Rahmat Hidayat; Erizal Erizal; Muhammad Halil (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of heat treatment on the hardness level of ST 37 steel material used in the press cage component, particularly after quenching using two different cooling media: seawater and SAE 40 oil. The press cage is a crucial component in screw press machines that operates under high pressure and requires optimal mechanical strength, including sufficient material hardness. The research method involved heating the specimens at 850°C for 30 minutes, followed by quenching using each of the cooling media. Hardness testing was conducted using the Rockwell method at five test points on each specimen. The results showed that the untreated specimen had an average hardness value of 72.3 HRC. After heat treatment and quenching, hardness significantly increased, with an average value of 93.8 HRC for specimens cooled in seawater and 84.3 HRC for those cooled in SAE 40 oil. The highest hardness was achieved using seawater due to its rapid cooling rate, which promotes the formation of martensitic structures. In contrast, quenching with SAE 40 oil produced lower hardness results because of its slower heat dissipation process. These findings indicate that the type of cooling medium has a significant impact on the mechanical properties of the material after heat treatment.